"Less‐than‐fluent" and culturally connected: Language learning and cultural fluency as research methodology. Issue 1 (15th June 2017) - Drozdzewski, Danielle
Abstract : The purpose of this paper is to critically explore language learning and cultural fluency as a research methodology. Deploying an auto‐ethnographic approach, I scrutinise my programme of language learning and forays into the cultural to highlight how knowledge of the cultural contexts of a language, and not just the language itself, have provided nuanced insights into Polish cultural memory and identity. The paper's specific contribution is to agitate for a greater recognition of the value of cultural understanding and language learning as a distinct methodological approach. I track how the process of learning the Polish language and its cultural intricacies has included both acts of speaking and comprehending how words are (re)presented in their cultural contexts.